Multiple strain analysis of Streptomyces species from Philippine marine sediments reveals intraspecies heterogeneity in antibiotic activities - Chuckcris P. Tenebro (Nature Portfolio, 2021)
Abstract The marine ecosystem has become the hotspot for finding antibiotic-producing actinomycetes across the globe. Although marine-derived actinomycetes display strain-level genomic and chemodiversity, it is unclear whether functional traits, i.e., antibiotic activity, vary in near-identical Streptomyces species. Here, we report culture-dependent isolation, antibiotic activity, phylogeny, biodiversity, abundance, and distribution of Streptomyces isolated from marine sediments across the west-central Philippines. Out of 2212 marine sediment-derived actinomycete strains isolated from 11 geographical sites, 92 strains exhibited antibacterial activities against multidrug-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The 16S rRNA and rpoB gene sequence analyses confirmed that antibiotic-producing strains belong to the genus Streptomyces, highlighting Streptomyces parvulus as the most dominant species and three possible new species. Antibiotic-producing Streptomyces strains were highly diverse in Southern Antique, and species diversity increase with marine sediment depth. Multiple strains with near-identical 16S rRNA and rpoB gene sequences displayed varying strength of antibiotic activities. The genotyping of PKS and NRPS genes revealed that closely related antibiotic-producing strains have similar BGC domains supported by their close phylogenetic proximity. These findings collectively suggest Streptomyces' intraspecies adaptive characteristics in distinct ecological niches that resulted in outcompeting other bacteria through differential antibiotic production.